2017
DOI: 10.1016/j.pec.2017.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous mental associations with the words “side effect”: Implications for informed and shared decision making

Abstract: Objective To gain insight into patients’ medical decisions by exploring the content of laypeople’s spontaneous mental associations with the term “side effect.” Methods An online cross-sectional survey asked 144 women aged 40–74, “What are the first three things you think of when you hear the words ‘side effect?’” Data were analyzed using content analysis, chi-square, and Fisher’s exact tests. Results 17 codes emerged and were grouped into 4 themes and a Miscellaneous category: Health Problems (70.8% of par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
(40 reference statements)
1
6
0
Order By: Relevance
“…Positive experiences also seem to be a contributing factor in decision making, though to a lesser extent. This is consistent with findings by Izadi and colleagues [45] which suggest that patient decision making may be driven by both affective processes and arguments presented by the psychiatrist, notwithstanding the fact that patients also seek information on the positive and negative effects of antipsychotic medication from multiple sources, in order to arrive at a decision [30]. Our study found that negative experiences with medication were more prominent among responses than positive ones, and these experiences tend to stay with the patient over many years and affect future decision making.…”
Section: Discussionsupporting
confidence: 94%
“…Positive experiences also seem to be a contributing factor in decision making, though to a lesser extent. This is consistent with findings by Izadi and colleagues [45] which suggest that patient decision making may be driven by both affective processes and arguments presented by the psychiatrist, notwithstanding the fact that patients also seek information on the positive and negative effects of antipsychotic medication from multiple sources, in order to arrive at a decision [30]. Our study found that negative experiences with medication were more prominent among responses than positive ones, and these experiences tend to stay with the patient over many years and affect future decision making.…”
Section: Discussionsupporting
confidence: 94%
“…It has been proposed that the side effect profile of chemoprevention medications, coupled with wide-ranging concerns about the emotional impact of taking a medication, leads to medication avoidance. Specifically, women might decide to avoid chemoprevention because of the affect-laden responses associated with the term “side effect” and their belief that these medications will increase, rather than decrease, their level of health-related stress [39]. [4042] Concerns about possible side effects, such as uterine cancer, thromboembolism, and menopausal symptoms, are the primary reasons why women are reluctant to start breast cancer chemoprevention [4349].…”
Section: Discussionmentioning
confidence: 99%
“…Patients come in with progressive clinical improvement and are generally aware of their diagnosis, although it has usually been expressed in terms of high curative possibility [1]. It falls to the oncologist to open a probabilistic scenario in which both risks and benefits must be calculated and prognostic uncertainty, side effects, and actual benefit for each individual patient [2] described.…”
Section: Introductionmentioning
confidence: 99%
“…Medical oncologists believe that coping style is highly pertinent to making decisions about adjuvant treatment or active follow-up, dealing with treatment side effects, and the anxiety caused by prognostic uncertainty [2]. Likewise, it is commonly felt that treatment decision and probably tolerance are influenced by physician-patient rapport, by how information is communicated, and by patients’ interpretation of what they are told [3].…”
Section: Introductionmentioning
confidence: 99%